Prevalence and Genotype Distribution of High-Risk Human Papillomavirus Infection Among Sub-Saharan African Women: A Systematic Review and Meta-Analysis - Ayichew Seyoum; Nega Assefa; Tadesse Gure; Berhanu Seyoum; Andargachew Mulu; Adane Mihret (Frontiers Media S.A., 2022)
BackgroundAmong sub-Saharan African women, cervical cancer is steadily increasing with more than 75,000 new cases and 50,000 deaths annually. Due to the vast ethno geography variation, Africa harbors heterogeneous genotypes of HPV. High-risk HPV [hr HPV] genotypes such as hr HPV-16,−18,-35, and−52 are abundantly reported in sub-Saharan Africa. The purpose of this systematic review and meta-analysis is to generate an evidence on the prevalence and the genotype distribution of hr HPV among sub-Saharan African countries.MethodsThe review was conducted by following the preferred reporting items for systematic reviews and Meta-analysis. PubMed/Medline, Embase, Scopus, Google Scholar, Heath Technology assessment and Cochrane Library databases were used to retrieve published original studies between 2001 and 2021. It included studies that used PCR-based or hybrid testing to assess the presence of HPV DNA in a cervical biopsy, cervical swelling, and vaginal swelling. Statistical software for data science (STATA V16) software using a random-effects model was used to determine the pooled prevalence and type-specific distribution of HPV with 95% confidence intervals (CI). The I-squared statistic was used to describe the level of heterogeneity. The study protocol is registered on PROSPERO with reference number CRD42022311157.ResultsThe review included 27 studies conducted in 19 sub-Saharan countries. A total of 16,506 study participants from 27 studies were included in a systematic review and 5,303 of them were infected with the hr HPV infection. Out these, only 3,075 of them were eligible for meta-analysis. The incidence proportion of estimatesof hr HPV infection among study participants with different health conditions ranges from 10.7 to 97.2% while the pooled incidence proportion of estimates is 34% (95%CI: 29-39). Among 3,075 women, 424 (13.8%), 305 (9.9%) and 279 (9%) were infected with HPV-16,−52 and−18, respectively. HPV-16 and−52 are the main genotypes causing the hr HPV infection in the Eastern and Southern African sub-contents, whereas HPV-16 and−35 are the main genotypes in the Western African countries.ConclusionsDepending on several factors, especially women's health conditions, the high rate of hr HPV infection with inconsistent genotype distribution shows that it is a growing public health challenge in sub-Saharan African countries. Therefore, to implement a vaccination-based prevention strategy and be effective, considering factors associated with hr HPV infection is crucial.